Dostoevskij e il sillogismo (ENTHYMEMA, 2013)
This is the first Italian translation of Richard Peace’s essay Dostoevsky and the Syllogism, originally published in the 2005 volume of  Dostoevsky Studies, New Series. The essay outlines the peculiar reworking of the Aristotelian syllogism by characters in Dostoevsky’s novels in the light of the debate between the two major Russian philosophical schools of the 19th century:  Occidentalism and Slavophilism. Peace underlines how  Dostoevsky aims at showing how syllogistic reasoning is alien to the Russian way of thinking through the argumentative failures of its proponents.